Bovine tuberculosis in cattle from 1986 to 2012 in and around badger-culled areas of the RBCT - Hendy,David (PeerJ Preprints, 2016)
In 2007 the Independent Scientific Group (ISG) reported to the UK government the impact on bovine tuberculosis (TB) in cattle of a trial where badgers were culled between 1998 and 2005. This trial, known as the Randomised Badger Culling Trial (RBCT), was performed across 100 km2 (nominal) zones in the West of England. The results were based on a model of new herd incidence data. It was concluded that reactive culling generated overall detrimental effects, while proactive culling achieved very modest overall benefits at the cost of elevated incidence in surrounding areas. This work looks at more extensive RBCT data to examine if these findings hold true. Instead of presenting the results of a model, this work directly illustrates the data. The Animal and Plant Health Agency supplied this data in March 2016. Such data covers a greater number of years (1986 to 2012) and includes the prevalence of herd restrictions as well as herd incidence. Whilst the proactive culls substantially and sustainably reduced cattle TB in treated areas, such culls did not significantly increase TB in the surrounding areas. In fact New Herd Incidents (NHI’s) between 2006 and 2012 dropped by 28%, 1% and 18% in the treated, outer 2km ring, and combined areas respectively. Based on the number of NHI’s prevented since 1998, a break-even cost for a badger removal exercise was calculated to be £8,454 per km2. This figure may be under-estimated because it takes no account of any NHI’s prevented after 2012. The more limited reactive culls were found to have no significant impact. This applied to both the treated area and outer 2km ring. The data also showed that the culls only reduced confirmed TB with no significant impact on unconfirmed TB. This was also found by the ISG when they reported results in 2007. Arguments surrounding badger culling in the UK have been poorly based due to incomplete data. In view of this and media hype, it should be emphasised that after the first year of substantial culling across the study area, 9 years of data were needed to clearly see the full extent by which TB dropped in the RBCT. This has implications for the culls which started in South West England in 2013. If the current reporting delay of 20 months persists, it may be the autumn of 2023 at the earliest before the impact of these culls becomes clear. Also, if culls stop after year four in each zone, this risks benefits falling short of those achieved in the RBCT.
Keywords: bovine tuberculosis; badger culling; rbct